1999
DOI: 10.1002/(sici)1096-8644(199911)110:3<271::aid-ajpa2>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of mtDNA haplogroup X among Native North Americans

Abstract: Mitochondrial DNA (mtDNA) samples of 70 Native Americans, most of whom had been found not to belong to any of the four common Native American haplogroups (A, B, C, and D), were analyzed for the presence of Dde I site losses at np 1715 and np 10394. These two mutations are characteristic of haplogroup X which might be of European origin. The first hypervariable segment (HVSI) of the non-coding control region (CR) of mtDNA of a representative selection of samples exhibiting these mutations was sequenced to confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(61 citation statements)
references
References 29 publications
(40 reference statements)
3
55
0
3
Order By: Relevance
“…On the other hand, the HVS-I motif 16223-16325-16362 is found in Asia (mainly in conjunction with the transition at nt 150 in HVS-II), but as we have seen above, most of these mtDNAs belong to haplogroup G1a and a few to other minor sub-clades of haplogroup M. Summarizing these results, there is no evidence at this time for the occurrence of haplogroup D1 mt-DNAs in Asia, in contrast with the situation for haplogroup C1 mtDNAs. In addition to the major east Asian haplogroups A-D, the minor west Eurasian haplogroup X is also observed among Native (North) American mtDNAs (Forster et al 1996;Scozzari et al 1997;Brown et al 1998;Smith et al 1999). From the Native American haplogroup X data of Brown et al (1998) that combine HVS-I and HVS-II with RFLPs, we infer that there are two ma- 1 Mutations are transitions unless specified by suffixes and refer to changes from the African L3 root mtDNA.…”
Section: Haplogroup Specific Markers and Motifs In Native American Mtmentioning
confidence: 60%
“…On the other hand, the HVS-I motif 16223-16325-16362 is found in Asia (mainly in conjunction with the transition at nt 150 in HVS-II), but as we have seen above, most of these mtDNAs belong to haplogroup G1a and a few to other minor sub-clades of haplogroup M. Summarizing these results, there is no evidence at this time for the occurrence of haplogroup D1 mt-DNAs in Asia, in contrast with the situation for haplogroup C1 mtDNAs. In addition to the major east Asian haplogroups A-D, the minor west Eurasian haplogroup X is also observed among Native (North) American mtDNAs (Forster et al 1996;Scozzari et al 1997;Brown et al 1998;Smith et al 1999). From the Native American haplogroup X data of Brown et al (1998) that combine HVS-I and HVS-II with RFLPs, we infer that there are two ma- 1 Mutations are transitions unless specified by suffixes and refer to changes from the African L3 root mtDNA.…”
Section: Haplogroup Specific Markers and Motifs In Native American Mtmentioning
confidence: 60%
“…The St Laurence River is certainly an access possibility and X2a (X2a1 as inferred from HVS sequence in Smith et al 1999), has been found in 50% (3/6) of a small sample of Algonquianspeaking Mi'kmaqs who live around its estuary (Malhi et al 2001). Moreover X2a1 has been identified in aDNA from the extinct Beothuk of nearby Newfoundland (Kuch, et al 2007).…”
Section: Separating Genetics and Culture And Testing Model Predictionsmentioning
confidence: 98%
“…Both of the two X2a1a embedded subgroups include Sioux, while one of these (X2a1a1 ~4.3 ka) has Jemez and Nuu-Chah-Nulth on one branch and Sioux on the other, (the same Washington cluster from Nuu-Chah-Nulth in Vancouver Island, inferred as X2a1a1 from HVS sequence/RFLP in Brown et al 1998). A southeastern United States aDNA dispersal location is Florida (Figure 1), where pre-Columbian (~ 8 ka) aDNA evidence for X (inferred from sequence as X2a1a1*) has also been found (Smith et al 1999), consistent with the implied Early Holocene date of expansion of X2a1a.…”
Section: Separating Genetics and Culture And Testing Model Predictionsmentioning
confidence: 99%
“…Among Amerindian populations, five main haplogroups are prevalent (A, B, C, D, and X- [21,22]) [13,[23][24][25][26][27]. Asian populations share American haplogroups (A, B, C, and D), as well as other haplogroups (M, N, G, F, Z, Y, and R) that are described as specific to the Asian continent [28,29].…”
Section: Bioanthropology and Bioarchaeology Of Guajajaramentioning
confidence: 99%